Syphilis in the Americas: a protocol for a systematic review of syphilis prevalence and incidence in four high-risk groups, 1980–2016 - Kitayama, Ken (2017)
Background: Syphilis infection has recently resurfaced as a significant public health problem. Although there has been a tremendous amount of research on the epidemiology of syphilis, there has been limited work done to synthesize the extensive body of research and systematically estimate patterns of disease within high-risk groups in the Americas. The purpose of this systematic review and meta-analysis is to (1) summarize recent patterns of syphilis infection in North and South America among four high-risk groups (MSM, transgender women, sex workers, and incarcerated individuals) from 1980 to 2016, (2) identify and differentiate regional geographic epidemiologic characteristics, and (3) compare the epidemics of the economically developed countries of North America from the developing countries and public health systems of Latin America and the Caribbean. Methods/design: Primary studies reporting syphilis prevalence and/or incidence in at least one of the four high-risk groups will be identified from Medline/PubMed, Embase, Lilacs, SciELO, The Cochrane Library, Web of Science, Scopus, ProQuest, CINAHL, Clase, and Periódica, as well as "gray" literature sources (conference abstracts, country reports, etc.). Studies published from 1980 through 2016 will be included. Data will be extracted from studies meeting inclusion and exclusion criteria and a random effects meta-analysis of prevalence and incidence estimates will be conducted. Heterogeneity, risk of bias, and publication bias will be assessed. Pooled prevalence and incidence estimates will be calculated for comparisons based on geographic region, risk factors, and time period. Discussion: Our systematic review and meta-analysis aims to contribute to an improved understanding of global epidemiologic patterns of syphilis infection in most-at-risk populations. Through systematic classification of the existing literature, and comparison of disease patterns across regional, temporal and socio-behavioral differences, we hope to improve public health surveillance and improve efforts to control the spread of disease across the Americas. Systematic review registration: PROSPERO CRD42016047306.